PROSPEK DAN TANTANGAN USAHATANI TEMBAKAU MADURA - Fuad Hasan; Dwidjono Hadi Darwanto (SEPA: Jurnal Sosial Ekonomi Pertanian dan Agribisnis, 2013)
Tobacco  has  an important  role  in the  socio-economic  life of  the community, such  as  the  State  in  the  form  of  tax  revenue  and  foreign  exchange  earnings,employment,  the  income  of farmers,  laborers,  and  merchants,  as well as  revenue.  But on  the other hand,  under the pretext of  health,  development  and  trading  of tobacco began  to  get  legalized  opposition  through  regulations.  This  has  an  impact  on  the survival  of tobacco  farming, which in turn  have an impact  on the welfare of  farmers. This  paper  aims  to  discuss  the  prospects  and  challenges  facing  tobacco  farmers  inMadura.  In addition,  tobacco farmers face problems: marketing  systems, productivity, and bargaining position. Alternative solutions are 1) reduction in acreage planted; 2) replacement  of  plants;  3)  low  nicotine  tobacco  cultivation;  4)  diversification  of derivative products; 5) optimization of the institutional.